Art Therapy Aspects and Experience - Hanson, Jennifer Lynn (My University, 2015)
A review of several aspects of interest pertaining to Art therapy including terms Art therapy, Metaphors, experiencing Resistance, Nature based therapy, Chemical addiction recovery, Co-Occurring Disorder, Mindfulness mediation, Models of therapy, Positive Psychology and Flow. An account of intern experiences in group art therapy sessions at an inpatient drug and alcohol addiction rehabilitation facility. Advice to beginning Art therapists is interwoven throughout.
Keywords: Rehabilitation; Art Therapy; Nature based therapy; Visual Arts; Mindfulness; Positive Psychology; Addiction; Recovery; Group Therapy